Penerapan Safety Management System pada AMTO 147D-13 Program Studi Teknologi Pemeliharaan Pesawat Udara Politeknik Penerbangan Makassar - Octavianie, Adhitya (Politeknik Penerbangan Makassar, 2020)
Aviation Safety is absolutely desirable by all the stakeholders in the aviation industry. It became a serious matter which why it is continuously strived to make it happen. Accidents may occur for some reason. Natural factors, human factors, or even the system’s failure factors are possibly to be a direct or indirect cause of accidents. Shaping up the safety culture and awareness in each organization will positively contribute to aviation safety. And these things are related to the success of Safety Management System implementation in each organization or entity. The purposes of this research are to find out how was Safety Management System was carried out in AMTO 147 D-13 Prodi TPPU Politeknik Penerbangan Makassar and also to identify the possible problems and obstacles to its implementation. This research is done in the qualitative descriptive method through an interview with the SMS Manager and key persons of AMTO 147 D-13 Prodi TPPU Politeknik Penerbangan Makassar, AMTO’s personnel questionnaire, observation, and documentation. Through GAP analysis, SMS indicators were compared in actual and ideal conditions. The research data shows a quite significant failure on SMS indicators which were mentioned in the SMS Manual of AMTO 147 D-13 Prodi TPPU Politeknik Penerbangan Makassar. A different level of comprehension and awareness about the SMS implementation importance in management and staff levels was a great contribution to the SMS implementation that was not yet carried out at the maximum.